Ecopoetic Place-Making Nature and Mobility in Contemporary American Poetry - Rauscher, Judith (Literary Ecologies, 2023)
American ecopoetries of migration explore the conflicted relationships of mobile subjects to the nonhuman world and thus offer valuable environmental insight for our current age of mass mobility and global ecological crisis. In Ecopoetic Place-Making, Judith Rauscher analyzes the works of five contemporary American poets of migration, drawing from ecocriticism and mobility studies. The poets discussed in her study challenge exclusionary notions of place-attachment and engage in ecopoetic place-making from different perspectives of mobility, testifying to the potential of poetry as a means of conceptualizing alternative environmental imaginaries for our contemporary world on the move.